Phosphoinositide 5- and 3-phosphatase activities of a voltage-sensing phosphatase in living cells show identical voltage dependence - Keum, Dongil; Kruse, Martin; Kim, Dong-Il; Hille, Bertil; Suh, Byung-Chang (Proceedings of the National Academy of Sciences - PNAS, 2016)
Voltage-sensing phosphatases (VSPs) are homologs of phosphatase and tensin homolog (PTEN), a phosphatidylinositol 3,4-bisphosphate [PI(3,4)P2] and phosphatidylinositol 3,4,5-trisphosphate [PI(3,4,5)P3] 3-phosphatase. However, VSPs have a wider range of substrates, cleaving 3-phosphate from PI(3,4)P2 and probably PI(3,4,5)P3 as well as 5-phosphate from phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2] and PI(3,4,5)P3 in response to membrane depolarization. Recent proposals say these reactions have differing voltage dependence. Using Förster resonance energy transfer probes specific for different PIs in living cells with zebrafish VSP, we quantitate both voltage-dependent 5- and 3-phosphatase subreactions against endogenous substrates. These activities become apparent with different voltage thresholds, voltage sensitivities, and catalytic rates. As an analytical tool, we refine a kinetic model that includes the endogenous pools of phosphoinositides, endogenous phosphatase and kinase reactions connecting them, and four exogenous voltage-dependent 5- and 3-phosphatase subreactions of VSP. We show that apparent voltage threshold differences for seeing effects of the 5- and 3-phosphatase activities in cells are not due to different intrinsic voltage dependence of these reactions. Rather, the reactions have a common voltage dependence, and apparent differences arise only because each VSP subreaction has a different absolute catalytic rate that begins to surpass the respective endogenous enzyme activities at different voltages. For zebrafish VSP, our modeling revealed that 3-phosphatase activity against PI(3,4,5)P3 is 55-fold slower than 5-phosphatase activity against PI(4,5)P2; thus, PI(4,5)P2 generated more slowly from dephosphorylating PI(3,4,5)P3 might never accumulate. When 5-phosphatase activity was counteracted by coexpression of a phosphatidylinositol 4-phosphate 5-kinase, there was accumulation of PI(4,5)P2 in parallel to PI(3,4,5)P3 dephosphorylation, emphasizing that VSPs can cleave the 3-phosphate of PI(3,4,5)P3.